Preparation method of recoverable photo-thermal response type rosin-based self-repairing anticorrosive coating
By combining the rosin derivative with Cu2+, a photothermal-responsive polyurethane coating is formed. It uses near-infrared light to activate it, and the problem of difficult local repair of thermoset polymer materials is solved, which achieves rapid repair of the coating and excellent mechanical properties. Outstanding photothermal self-repairing performance and recyclability.
Patent Information
- Application Number
- CN202411360553.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
The existing thermoset polymer materials are difficult to partially repair during use, and traditional photothermal agents have low photothermal conversion efficiency and poor dispersion, making it difficult to achieve high-performance self-repair anti-corrosion coatings.
The combination of rosin derivatives and Cu2+ is used to form a photothermal-responsive polyurethane coating through near-infrared light activation. The rosin acrylic acid, GMA esterides, butadiene oxime and adipic acid dihydrazide are used to form excellent photothermal conversion. Capable of anticorrosion coating.
It realizes rapid repair of the coating under near-infrared light, excellent mechanical properties and recyclability, solves the problems of poor adhesion and mechanical properties of traditional coatings, and has outstanding photothermal self-repairing performance and recyclability.
Smart Images

Figure BDA0005064831780000071 
Figure HDA0005064831790000011 
Figure HDA0005064831790000012
Abstract
Description
Technical Field
[0001] The invention relates to the field of anti-corrosion coatings, and in particular to a method for preparing a recyclable photothermal responsive rosin-based self-repairing anti-corrosion coating. Background Art
[0002] Thermosetting polymers have excellent dimensional stability and creep resistance and have been widely used in various electronic and energy devices, but they are difficult to reprocess and recycle. As non-renewable resources such as petroleum are gradually decreasing, there is an urgent need to develop new sustainable materials as alternatives to thermosetting polymers, and bio-based thermosetting polymers have emerged.
[0003] Thermosetting polymer materials have internal damage during use and are difficult to last. Polymer materials with self-healing properties can provide better durability and sustainability for equipment and devices. Conventional stimulation methods such as heating and solvents cannot achieve local repair and require a lot of energy.
[0004] With the development of optical technology, the repair of materials by remotely controlling light has received increasing attention. However, some of the currently used photothermal agents (carbon nanotubes, graphene, and polydopamine, etc.) have problems such as low photothermal conversion efficiency and poor dispersibility. Compared with traditional overall heating methods, light energy is cheap, readily available, environmentally friendly, energy-saving, and safe. At the same time, the spatial flexibility and remote controllability of light energy provide more possibilities for precise, local response repair of materials.
[0005] Most of the current polyurethane coatings use petroleum-based monomers as soft segments, making it difficult to obtain green and environmentally friendly high-performance self-healing anti-corrosion coatings. At the same time, the coatings have poor adhesion and mechanical properties, and do not have self-healing properties. The unique rigid tricyclic phenanthrene skeleton of natural renewable resources rosin enhances the mechanical properties of the material, thereby improving the adhesion and mechanical durability of the coating; while Cu 2+ Under the action of near-infrared light, dd energy band transition can occur, which can convert light energy into heat energy. Therefore, by introducing rosin derivatives into polyurethane coatings, the use of petroleum-based monomers can be reduced, its mechanical properties and thermal stability can be enhanced, and the introduction of Cu 2+ The coating is endowed with rapid photothermal conversion and photothermal repair capabilities, thereby achieving excellent recyclability and rapid light response characteristics of the coating. Summary of the invention
[0006] In view of the above technical problems, the present invention invents a method for preparing a rosin-based self-healing anti-corrosion coating, aiming to obtain a rosin-based self-healing anti-corrosion coating with excellent recyclability, photothermal self-healing performance, and photothermally driven shape memory.
[0007] To achieve the above purpose, the technical solution provided by the present invention is as follows:
[0008] A recyclable photothermal responsive rosin-based self-repairing anti-corrosion coating comprises the following steps:
[0009] (1) adding toluene 2,4-diisocyanate, isophorone diisocyanate, polycaprolactone diol, a catalyst and an organic solvent into a reactor, introducing N2 to deoxygenate, stirring and reacting at 55° C. and 300 r / min for 1 hour to obtain a polyurethane (PU) prepolymer solution;
[0010] (2) at 55° C., add acrylic rosin and GMA ester RAG and / or butanediol to the prepolymer solution of step (1), and stir at 300 r / min for 1 h;
[0011] (3) adding diacetyl oxime to the solution of step (2) at 55°C, stirring at 300 r / min for 1 h;
[0012] (4) Add adipic acid dihydrazide to the solution of step (3) at 55°C, and stir at 300 r / min for 6 h;
[0013] (5) Add copper chloride to the solution of step (4) at 55°C and stir at 300 r / min for 1 h;
[0014] (6) The polymer solution obtained in step (5) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 48 hours to obtain a recyclable photothermal responsive rosin-based self-healing anti-corrosion coating.
[0015] In step (1), according to the weight ratio, toluene 2,4-diisocyanate is 30 parts, isophorone diisocyanate is 70 parts, polycaprolactone diol is 50 parts, the catalyst is 5 parts, and the solvent is 350 parts.
[0016] The molecular weight of the polycaprolactone diol described in step (1) is 1000 g / mol.
[0017] The catalyst described in step (1) is dibutyltin dilaurate, and the organic solvent is N,N-dimethylacetamide or N,N-dimethylformamide.
[0018] In step (2), according to the weight ratio, RAG is 0-25 parts and butanediol is 5-0 parts.
[0019] In step (3), the amount of diacetyl oxime is 12.5 parts by weight.
[0020] In step (4), the amount of adipic acid dihydrazide is 12.5 parts by weight.
[0021] In step (5), the amount of cupric chloride is 5 parts by weight.
[0022] The stirring is mechanical stirring.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The method of the present invention uses acrylic rosin and GMA ester RAG as rigid monomers, copper chloride as a dynamic monomer and photothermal agent, and then cooperates with the dynamic properties of dimethylglyoxime and adipic acid dihydrazide to prepare a rosin-based anticorrosion coating with excellent photothermal conversion ability, photothermal self-healing performance, mechanical properties, photothermal-driven shape memory and recyclability through a simple one-pot method. The coating can reach 121.6°C in 20 seconds under near-infrared light irradiation, and the damaged part can be completely repaired in 40 seconds under near-infrared light irradiation. Furthermore, the designed optical actuator exhibits fast and excellent photoactuated performance under near-infrared light irradiation, and has great potential applications in the fields of smart anticorrosion coatings and flexible electronics.
[0025] 2. The present invention uses cupric chloride as a photothermal agent, which has good compatibility and dispersibility in the coating, thereby forming a continuous heat conduction network, solving the problem of easy aggregation and uneven heat transfer of traditional photothermal agents. Under the action of near-infrared light, the coating has outstanding photothermal conversion capabilities, which can achieve remote, precise, energy-saving and environmentally friendly rapid repair.
[0026] 3. The present invention uses diacetyl oxime that can form oxime-carbamate bonds, adipic acid dihydrazide that can form high-density hydrogen bonds, and cupric chloride that can form metal coordination bonds as dynamic monomers, and synergistically improves the mechanical durability and self-healing properties of the coating through the strategy of "accumulating weakness into strength", thereby extending the service life of the coating.
[0027] 4. The present invention utilizes rosin derivative-based polyols to prepare an anti-corrosion coating, thereby increasing the added value of rosin, a natural renewable resource, while enhancing the mechanical properties and adhesion of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the light-to-heat conversion diagram of the coating.
[0029] Figure 2 This is a diagram showing the self-healing effect of the coating.
[0030] Figure 3 is a photothermally driven shape memory map of the coating.
[0031] Figure 4 It is the hot pressing recovery performance diagram of the coating.
[0032] Figure 5 are the polarization curves and Nyquist plots of blank tinplate and coating.
[0033] Figure 6are the polarization curves and Nyquist plots of the original and repaired coatings. DETAILED DESCRIPTION
[0034] The following is a detailed description in conjunction with the specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. The raw materials and reagents used in the examples are all commercially available unless otherwise specified.
[0035] The monomeric rosin ester RAG used in the examples was prepared according to the method described in application number CN105647389.
[0036] Example 1
[0037] (1) adding 30 parts of toluene 2,4-diisocyanate, 70 parts of isophorone diisocyanate, 50 parts of polycaprolactone diol, 5 parts of a catalyst and 350 parts of an organic solvent into a reactor, introducing N2 to deoxygenate, and mechanically stirring at 55° C. and 300 r / min for 1 hour to obtain a polyurethane prepolymer solution;
[0038] (2) At 55° C., 5 parts of butanediol were added to the prepolymer solution of step (1), and the mixture was stirred at 300 r / min for 1 h;
[0039] (3) At 55° C., 12.5 parts of dimethylglyoxime were added to the solution of step (2), and the mixture was stirred at 300 r / min for 1 h;
[0040] (4) At 55° C., 12.5 parts of adipic acid dihydrazide were added to the solution of step (3), and the mixture was stirred at 300 r / min for 6 h;
[0041] (5) Add 5 parts of copper chloride to the solution of step (4) at 55°C, and stir at 300 r / min for 1 h;
[0042] (6) The polymer solution obtained in step (5) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 48 hours to obtain a recyclable photothermal responsive rosin-based self-healing anti-corrosion coating.
[0043] Example 2
[0044] (1) Prepare a polyurethane prepolymer solution in the same manner as in Example 1;
[0045] (2) At 55° C., 25 parts of esterified RAG were added to the prepolymer solution of step (1), and stirred at 300 r / min for 1 h;
[0046] (3)-(6) Same as Example 1.
[0047] Example 3
[0048] (1) Prepare a polyurethane prepolymer solution in the same manner as in Example 1;
[0049] (2) At 55° C., 10 parts of esterified RAG and 3 parts of butanediol were added to the prepolymer solution of step (1), and stirred at 300 r / min for 1 h;
[0050] (3) The rest of the process is the same as in Example 2 to obtain a recyclable photothermal responsive rosin-based self-repairing anti-corrosion coating.
[0051] Example 4
[0052] (1) Prepare a polyurethane prepolymer solution in the same manner as in Example 1;
[0053] (2) At 55° C., 15 parts of esterified RAG and 2 parts of butanediol were added to the prepolymer solution of step (1), and stirred at 300 r / min for 1 h;
[0054] (3) The rest of the process is the same as in Example 2 to obtain a recyclable photothermal responsive rosin-based self-repairing anti-corrosion coating.
[0055] Comparison Example
[0056] (1)-(4) are the same as in Example 2.
[0057] (5) The polymer solution obtained in step (4) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 48 hours to obtain a recyclable rosin-based self-repairing anti-corrosion coating.
[0058] Implementation Effect
[0059] (1) The coating obtained in Example 1 has a smooth surface and good bonding strength with the substrate; the tensile strength reaches 12.5 MPa, the elongation at break is 1192%, and the water contact angle is 98.3°.
[0060] The photothermal self-healing property of the anti-corrosion coating is achieved by scratching the coating surface with a razor blade and then irradiating it with near-infrared light (λ = 808 nm, 0.5 W cm -2 ) to observe the repair of scratches.
[0061] When the coating was irradiated with near-infrared light for 5 seconds, the surface temperature quickly rose to 74.5°C. After the time was extended to 20 seconds, the surface temperature reached 121.6°C, showing excellent photothermal conversion ability (see Figure 1 In addition, after the coating was irradiated with near-infrared light for 20 seconds, the scratch width was significantly reduced, and the scratch was completely repaired when the irradiation time was extended to 40 seconds, indicating that the coating has outstanding photothermal self-healing properties (see Figure 2 ).
[0062] (2) The coating obtained in Example 2 has a smooth surface and good bonding strength with the substrate; the tensile strength reaches 27.4 MPa, the elongation at break is 731%, and the water contact angle is 103.2°.
[0063] The photothermal-driven shape memory property of the anti-corrosion coating is to fix the film into temporary shapes of "W" and "bud" respectively, then irradiate it with near-infrared light and observe the recovery of the temporary shapes.
[0064] The temporary shape can respond quickly under near-infrared light irradiation and gradually recover to the original shape within 40 seconds, showing fast and excellent near-infrared light actuation performance (see Figure 3 ).
[0065] (3) The coating obtained in Example 3 has a smooth surface and good bonding strength with the substrate.
[0066] The recyclability of the anti-corrosion coating is tested by cutting the coating into pieces and hot pressing them at 130°C and 10MPa for 1h, and then using a universal tensile testing machine to test the mechanical properties and infrared spectrum of the recycled coating.
[0067] The shredded coating can form a uniform film again after hot pressing. After three recycling cycles, the tensile strength and elongation at break of the coating still reach 75.9% (20.8 MPa) and 78.3% (572.2%) of the original coating, respectively. The infrared spectra of the original and recycled coatings are basically the same, confirming its recyclability and excellent recycling stability (see Figure 4 ).
[0068] (4) The coating obtained in Example 4 has a smooth surface and good bonding strength with the substrate.
[0069] The coating was immersed in a 3.5 wt % sodium chloride solution for 30 min, and then the polarization curve and Nyquist curve were tested using an electrochemical workstation to study the anti-corrosion performance of the coating.
[0070] Corrosion current density, corrosion potential and capacitance ring radius are important parameters for measuring the corrosion resistance of coatings. The corrosion current density, corrosion potential and capacitance ring radius of blank tinplate are 2.822 μA cm -2 , -0.7231V and 3.2×10 3 Ωcm 2 In contrast, the tinplate coated with the polymer solution has a smaller corrosion current density (0.025 μA cm -2 ), the corrosion potential is closer to the positive value (-0.3547V), and it also has a higher capacitance ring radius (9.9×10 5 Ωcm 2 ), the coating has strong charge transfer resistance and excellent corrosion resistance (see Figure 5). In addition, the corrosion current density, corrosion potential and capacitance ring radius of the coating after damage-repair were 0.052 μA cm -2 , -0.4474V and 6.1×10 5 Ωcm 2 , still maintain good corrosion resistance (see Figure 6 ).
[0071] (5) The coating obtained in Example 5 has a smooth surface and good bonding with the substrate; the tensile strength reaches 3.1 MPa, the elongation at break is 557%, and the water contact angle is 94.6°. It has certain recyclability, but no light and heat self-healing performance, and the anti-corrosion performance is average (Table 1).
[0072] In summary, the present invention prepares a rosin-based anti-corrosion coating with excellent photothermal conversion ability, photothermal self-healing performance, mechanical properties, photothermal-driven shape memory and recyclability through a simple one-pot method. Based on the excellent photothermal conversion ability and dynamic characteristics of the copper coordination bond, the resulting coating has outstanding photothermal self-healing performance and recyclability. Due to the unique rigid tricyclic phenanthrene skeleton of rosin, the coating exhibits good adhesion and excellent mechanical properties. The designed optical actuator exhibits fast and excellent photoactuated performance under near-infrared light irradiation, and has great potential applications in the fields of intelligent anti-corrosion coatings and flexible electronics.
[0073] Table 1 Product form and related performance data
[0074]
Claims
1. A method for preparing a recyclable photothermal responsive rosin-based self-repairing anti-corrosion coating, characterized in that: The following steps are included: (1) adding toluene 2,4-diisocyanate, isophorone diisocyanate, polycaprolactone diol, a catalyst and an organic solvent into a reactor, introducing nitrogen to remove oxygen, stirring at 55° C. and 300 r / min for 1 hour to obtain a polyurethane prepolymer solution; (2) at 55° C., adding acrylic rosin and glycidyl methacrylate (GMA) ester (RAG) and / or butanediol to the prepolymer solution of step (1), maintaining stirring at 300 r / min for 1 h; (3) adding diacetyl oxime to the solution of step (2) at 55°C, stirring at 300 r / min for 1 h; (4) Add adipic acid dihydrazide to the solution of step (3) at 55°C, and stir at 300 r / min for 6 h; (5) Add copper chloride to the solution of step (4) at 55°C and stir at 300 r / min for 1 h; (6) The polymer solution obtained in step (5) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 48 hours to obtain a recyclable photothermal responsive rosin-based self-healing anti-corrosion coating.
2. The preparation method according to claim 1, characterized in that: In step (1), according to the weight ratio, toluene 2,4-diisocyanate is 30 parts, isophorone diisocyanate is 70 parts, polycaprolactone diol is 50 parts, the catalyst is 5 parts, and the solvent is 350 parts.
3. The preparation method according to claim 1, characterized in that: The molecular weight of the polycaprolactone diol described in step (1) is 1000 g / mol.
4. The preparation method according to claim 1, characterized in that: The catalyst described in step (1) is dibutyltin dilaurate, and the organic solvent is N,N-dimethylacetamide or N,N-dimethylformamide.
5. The preparation method according to claim 1, characterized in that: In step (2), according to the weight ratio, RAG is 0-25 parts and butanediol is 0-5 parts.
6. The preparation method according to claim 1, characterized in that: In step (3), the amount of diacetyl oxime is 12.5 parts by weight.
7. The preparation method according to claim 1, characterized in that: In step (4), the amount of adipic acid dihydrazide is 12.5 parts by weight.
8. The preparation method according to claim 1, characterized in that: In step (5), the amount of cupric chloride is 5 parts by weight.
9. The preparation method according to claim 1, characterized in that: The stirring is mechanical stirring.
